2019
DOI: 10.1101/634063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of global signal regression on DCM estimates of noise and effective connectivity from resting state fMRI

Abstract: The influence of the global BOLD signal on resting state functional connectivity in fMRI data remains a topic of debate, with little consensus. In this study, we assessed the effects of global signal regression (GSR) on effective connectivity within and between resting-state networks -as estimated with dynamic causal modelling (DCM) for resting state fMRI (rsfMRI). DCM incorporates a forward (generative) model that quantifies the contribution of different types of noise (including global measurement noise), ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Variation in preprocessing pipelines in particular can be a significant barrier to the accurate comparison of findings across neuroimaging studies. For comparison of motion correction pipelines, see Parkes et al (2018); for global signal regression see Almgren et al (2020) and Aquino et al (2020); and for motion correction in diffusion imaging pipelines, see Oldham et al (2020). The optimization and standardization of these pipelines-in conjunction with replication and comparison between psychedelicsmay be essential.…”
Section: R Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in preprocessing pipelines in particular can be a significant barrier to the accurate comparison of findings across neuroimaging studies. For comparison of motion correction pipelines, see Parkes et al (2018); for global signal regression see Almgren et al (2020) and Aquino et al (2020); and for motion correction in diffusion imaging pipelines, see Oldham et al (2020). The optimization and standardization of these pipelines-in conjunction with replication and comparison between psychedelicsmay be essential.…”
Section: R Methodological Considerationsmentioning
confidence: 99%
“…Hierarchical predictive coding is a mechanistic account of how the brain processes information (Friston, 2008). It is supported by empirical evidence (Mumford, 1992;Rao and Ballard, 1999) and informed by our understanding of synaptic communication (Adams et al, 2013;Friston, 2020;Hobson et al, 2021). Noting the neuromodulatory role of serotonergic neurotransmission (Picard and Friston, 2014) and the influence of psychedelics upon these receptors, it provides a unifying account of psychedelic subjective and therapeutic effects.…”
Section: R Methodological Considerationsmentioning
confidence: 99%
“…We did not conduct global signal regression, because a previous study found that data without global signal regression are more informative for estimation of effective connectivity. 38 We used mean frame-wise displacement -which considers measures of voxel-wise differences in motion in its deri vation 39 -as a measure of the micro-head motion of each participant. 40 Participants whose mean frame-wise displacement was greater than 3 interquartile ranges from the sample median or who had fewer than 100 "good" volumes of data (frame-wise displacement threshold ≤ 0.2 mm) were to be excluded from further analysis, but no participant was excluded based on this motion threshold.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…In addition, cerebrospinal fluid and white matter signals were added as regressors to the model in order to reduce the influence of artifacts caused by physiological signal sources on the results. The global signal was not added to the model, as there is no consensus on the use of this regressor ( Almgren et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%